Quadratic forms and Sobolev spaces of fractional order. Issue 3 (16th April 2019) - Bux, Kai‐Uwe; Kassmann, Moritz; Schulze, Tim
Abstract: We study quadratic functionals on L 2 ( R d ) that generate seminorms in the fractional Sobolev space H s ( R d ) for 0 < s < 1 . The functionals under consideration appear in the study of Markov jump processes and, independently, in recent research on the Boltzmann equation. The functional measures differentiability of a function f in a similar way as the seminorm of H s ( R d ) . The major difference is that differences f ( y ) − f ( x ) are taken into account only if y lies in some double cone with apex at x or vice versa. The configuration of double cones is allowed to be inhomogeneous without any assumption on the spatial regularity. We prove that the resulting seminorm is comparable to the standard one of H s ( R d ) . The proof follows from a similar result on discrete quadratic forms in Z d, which is our second main result. We establish a general scheme for discrete approximations of nonlocal quadratic forms. Applications to Markov jump processes are discussed.